GGR critical review of analytical developments in 2006-2007 - Hergt, J.; Bédard, L.; Brueckner, S.; Jochum, K.; Linge, Kathryn; Sylvester, P.; Wiedenbeck, M.; Woodhead, J. (Wiley-Blackwell Publishing, 2008)
In 2005 the Geostandards and Geoanalytical Research editorial team, in the true spirit of scientific endeavour, embarked on an experiment of our own. We decided to trial a new kind of review, somewhat different from those more typically observed in journals, and one that would provide readers with a summary of analytical developments across a broad range of topics appropriate to the Earth sciences. The first contribution of this kind appeared in 2005, and reported on developments in 2003 (Hergt et al. 2005). The second, this time a biennial review, was published in 2006 and reported on highlights of the 2004 and 2005 literature (Hergt et al. 2006). Based on reprint requests, positive remarks at conferences and strong citations we consider the experiment a resounding success and proudly present here the third in this series. This comprises six individual review sections that cover the main analytical technologies and topical application fields in geoanalysis and geochemistry, including geological and environmental reference materials, ICP-thermal and secondary ionisation-mass spectrometry, as well as neutron activation analysis, X-ray fluorescence and atomic absorption spectrometry. © 2008 The Authors. Journal compilation © 2008 International Association of Geoanalysts.